2023
DOI: 10.3390/plants12040726
|View full text |Cite
|
Sign up to set email alerts
|

Canola with Stacked Genes Shows Moderate Resistance and Resilience against a Field Population of Plasmodiophora brassicae (Clubroot) Pathotype X

Abstract: Genetic resistance is a cornerstone for managing clubroot (Plasmodiophora brassicae). However, when used repeatedly, a clubroot resistance (CR) gene can be broken rapidly. In this study, canola inbred/hybrid lines carrying one or two CR genes (Rcr1/CRaM and Crr1rutb) were assessed against P. brassicae pathotype X by repeated exposure to the same inoculum source under a controlled environment. Lines carrying two CR genes, either Rcr1 + Crr1rutb or CRaM + Crr1rutb, showed partial resistance. Selected lines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This observation aligns with previous reports on the effectiveness of certain CR genes and gene combinations in conferring resistance to specific P . brassicae pathotypes ( Strelkov et al., 2018 ; Sedaghatkish et al., 2019 ; Tonu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation aligns with previous reports on the effectiveness of certain CR genes and gene combinations in conferring resistance to specific P . brassicae pathotypes ( Strelkov et al., 2018 ; Sedaghatkish et al., 2019 ; Tonu et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this partial resistance is derived from Crr1 rutb in line 20, as the inbred line carrying CRa M alone was susceptible. In a prior study, Tonu et al. (2023) reported that line 20 produced in different batches may vary in resistance to pathotype X, with some batches showing almost immunity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations